2015
DOI: 10.1515/cclm-2014-0572
|View full text |Cite
|
Sign up to set email alerts
|

Auto-validation of complete blood counts in an outpatient’s regional laboratory

Abstract: We conclude that very high auto-validation rates are possible in outpatient general laboratories, leading to conformity in the validation process and a considerable estimated savings in technician time. Further studies are needed in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Once the algorithm is technically set up, decision upon whether all tests or specific test panels will be subject to AV should be made. The results of the survey showed that AV is most commonly applied to routine biochemistry tests, haematology and coagulation tests, and similar results are reported in literature (2,(14)(15)(16)(17). Some studies reported the use of AV for special biochemistry tests, i.e.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Once the algorithm is technically set up, decision upon whether all tests or specific test panels will be subject to AV should be made. The results of the survey showed that AV is most commonly applied to routine biochemistry tests, haematology and coagulation tests, and similar results are reported in literature (2,(14)(15)(16)(17). Some studies reported the use of AV for special biochemistry tests, i.e.…”
Section: Discussionsupporting
confidence: 73%
“…Most participants answered that validation was performed on less than 500 samples. However, data about the number of samples included in the validation process is inconsistent throughout literature (2,14,17). Since there are no guidelines for the number of samples required for validation, Working Group for Post-analytics of the CSMBLM recommends that each laboratory decides on how many samples will be included in the validation, depending on the number of patients/ samples in the laboratory and test panel included in AV (3).…”
Section: Discussionmentioning
confidence: 99%
“…Modern laboratory information systems (LIS) have the ability to autovalidate test results in coagulation laboratories decreasing pre‐analytic and probably analytic and postanalytic errors as well as decreasing turnaround time in hospitalized patients . We recently reported complete blood count autovalidation rates of 97.6% after rejecting results requiring validation to determine the need for a peripheral smear review and/or sample rerun, and 92.9% after including reflex testing to determine the etiology of normocytic and microcytic anemia . Indications for coagulation reflex testing, however, are different from complete blood counts.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published literature to date is limited to autoverification rules written in the hematology analyzer and the LIS. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 Reported autoverification rates for CBC results have ranged from 63% when rules were built in the analyzer 10 to 81% when written in LIS. 12 Similarly in coagulation, reported autoverification rates have ranged from 65% to 82%.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 10 High rates of LIS-based autoverification were achieved in an outpatient hematology/coagulation laboratory; however, outpatient samples may be less complex to result than predominantly inpatient population. 6 , 7 We were able to find 1 report of a hematology laboratory that built autoverification rules in middleware and these authors used similar instrumentation and middleware as our laboratory. 13 They achieved an autoverification rate of 93.5% for CBC and 89.9% for individual CBC components, which was similar to our results of 97.2% for all CBCD and 88.3% for WBC differentials.…”
Section: Discussionmentioning
confidence: 99%